The Quality and Cultural Safety of Online Osteoarthritis Information for Affected Persons and Health Care Professionals: Content Analysis - Smita Dhakal; Shermeen Merani; Vandana Ahluwalia; Marisa Battistella; Cornelia M Borkhoff; Glen Stewart Hazlewood; Aisha Lofters; Deborah A Marshall; Crystal MacKay; Anna R Gagliardi (JMIR Publications, 2024)
BackgroundOsteoarthritis is more prevalent and severe among women than among men, but women are less likely to access early diagnosis and first-line management, particularly racialized immigrant women. Previous research advocated for greater access to culturally safe osteoarthritis information for both diverse women and health care professionals. The internet can reduce disparities by facilitating access to health information, but online materials can vary in quality. ObjectiveThis study aimed to assess the quality and cultural safety of online osteoarthritis materials for persons affected by osteoarthritis and health care professionals. MethodsContent analysis was used to describe publicly available materials on osteoarthritis first-line management developed by Canadian organizations for affected persons or health care professionals. Searching, screening, and data extraction were performed in triplicate. We identified materials by searching Google, MEDLINE, and references of osteoarthritis-relevant guidelines and policies, and consulting our research team and collaborators. We assessed quality using DISCERN (University of Oxford) and a compiled framework for affected persons and health care professionals. We compiled frameworks to assess cultural safety. We derived an overall score, categorized as low (<50%), moderate (50%-69%), or high (≥70%+) for criteria met. ResultsAfter screening 176 items and eliminating 129, we included 47 osteoarthritis materials published between 2013 and 2023. Of those, 43 were for persons with osteoarthritis, most were developed by charities (n=31, 72.1%), based on expert advice (n=16, 55.2%), and in the format of booklets (n=15, 34.9%) or text on web pages (n=10, 23.3%). Of those, 23.3% (10/43) low, 46.5% (20/43) moderate, and 30.2% (13/43) high scored quality; and 25.6% (11/43), 48.8% (21/43), and 25.6% (11/43) were rated low, moderate, and high cultural safety, respectively. Of the 47 included osteoarthritis materials, 4 were for health care professionals. They were developed by a consortium (2/4, 50%), a charity (1/4, 25%), and a professional society (1/4, 25%), and largely based on expert advice (3/4, 75%). The format included infographics (3/4, 75%) and text on web pages (1/4, 25%). Of those, 25% (1/4), 25% (1/4), and 50% (2/4) were rated low, moderate, and high quality, respectively; and all were rated low for cultural safety. Quality and cultural safety did not appear to be associated with the characteristics of osteoarthritis materials (eg, type of developer, development method, and format). ConclusionsOverall, included osteoarthritis materials for persons with osteoarthritis and health care professionals were of low to moderate quality and cultural safety. These findings reveal the need for further efforts to improve existing or develop new osteoarthritis materials for both affected persons, including ethnoculturally diverse immigrant women, and health care professionals. Further research is needed to assess the quality and cultural safety of osteoarthritis materials developed by organizations outside of Canada and to establish a framework or instrument to assess cultural safety in the osteoarthritis context.